Strengthening the backbone - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
A country's infrastructure, and its transport system in particular, is very often seen as a key aspect of its development. Harbours, railways, roads and airports are literally the gateways that a country needs for exchange and communication, for its...